Familial MEN1 Syndrome Diagnosed on Functional Imaging: A Case Report with Clinical and Genetic Correlation - Kalshetty, Ashwini; Chalikandy, Ashwini (World Journal of Nuclear Medicine, 2023)
Multiple endocrine neoplasia, type 1 (MEN1) syndrome is an autosomal dominant disease characterized by tumors involving parathyroid, pituitary, and pancreas. The diagnosis is mostly clinical and by the presence of MEN1 gene mutation. We present a case with initial presentation of neuroendocrine tumor of pancreas whose ancillary findings on 68Ga-DOTATATE positron emission tomography-computed tomography helped in raising suspicion of MEN1, which was confirmed on genetic testing and family history. We emphasize the importance of using gestalt approach in such cases to avoid misdiagnosis or delay. Additionally, we describe the clinical profile of affected family members with their MEN1 gene mutation status, highlighting the gestalt approach again to uncover the unknowns.
Keywords: genetic; hyperparathyroidism; MEN1; NET; PET-CT; phenocopies